Validation of the Paediatric Food Allergy Quality of Life Questionnaire (PFA‐QL). Issue 3 (16th April 2013) - Knibb, Rebecca C.; Ibrahim, Nur F.; Petley, Rachel; Cummings, Amanda J.; King, Rosemary M.; Roberts, Graham; Erlewyn‐Lajeunesse, Michel; Lucas, Jane S. A.
Abstract Background The Paediatric Food Allergy Quality of Life Questionnaire (PFA‐QL) was the first tool to be developed for assessing health‐related quality of life (QoL) in children with food allergy. It has been used in a number of published studies, but has not been validated. Objective The aim of the current study was to validate child (PFA‐QL) and parent–proxy (PFA‐QL‐PF) versions of the scale in a specialist allergy clinic and in parents of children with food allergy. Methods For the clinic sample, a generic QoL scale (PedsQL) and the PFA‐QL were completed by 103 children (age 6–16 yrs) with peanut or tree nut allergy; test–retest reliability of the PFA‐QL was tested in 50 stable patients. For the non‐clinical sample, 756 parents of food allergic children completed the PFA‐QL‐PF, the Child Health Questionnaire (CHQ‐PF50), Food Allergy Quality of Life Parental Burden Scale (FAQL‐PB) and a Food Allergy Impact Measure. Results The PFA‐QL and PFA‐QL‐PF had good internal consistency (α's of 0.77–0.82), and there was moderate‐to‐good agreement between the generic‐ and disease‐specific questionnaires. The PFA‐QL was stable over time in the clinic sample, and in both samples, girls were reported to have poorer QoL than boys. Conclusions The PFA‐QL and PFA‐QL‐PF are reliable and valid scales for use in both clinical and non‐clinical populations. Unlike other available tools, they were developed and validated in the UK and thus provide a culture‐specific choice for research, clinical trials and clinical practice in the UK. Validation in other countries is now needed.